2017
DOI: 10.14791/btrt.2017.5.1.24
|View full text |Cite
|
Sign up to set email alerts
|

Fourth Ventricular Lesions in Metastatic Gliomas: A Rare Predilection?

Abstract: Over the course of five years, a total of ten cases were collected of glioma patients in whom a distant lesion at the fourth ventricle was noted. A ‘distant lesion’ was defined as a lesion with a normal appearing tissue bridge at imaging between the primary and secondary locations. Previous imaging of these patients was reviewed along with clinical history, course of therapy, and available histology. A review of the literature was performed with respect to present knowledge on patterns of glioma proliferation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…These recurrent patterns imply leptomeningeal dissemination (LMD) as the pathogenesis of ITR. Previous studies have reported that supratentorial GBM cells metastasize into the fourth ventricle or cerebellum via the cerebrospinal fluid (CSF) through an aqueduct from the third or lateral ventricle [ 5 , 14 ]. Moreover, tumor cells may disseminate through the CSF with a predilection to regions with slow CSF flow or gravity-dependent sites, such as the basal cisterns or posterior fossa [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…These recurrent patterns imply leptomeningeal dissemination (LMD) as the pathogenesis of ITR. Previous studies have reported that supratentorial GBM cells metastasize into the fourth ventricle or cerebellum via the cerebrospinal fluid (CSF) through an aqueduct from the third or lateral ventricle [ 5 , 14 ]. Moreover, tumor cells may disseminate through the CSF with a predilection to regions with slow CSF flow or gravity-dependent sites, such as the basal cisterns or posterior fossa [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…There still lacks efficient and effective treatment modalities for GBM dissemination control. Some polite studies revealed that stereotactic radiosurgery (SRS) might be helpful for a single, small lesion with the satisfactory disease control (19,47). For eligible patients, SRS might be an ideal choice to alleviate suffering and prolong survival.…”
Section: Discussionmentioning
confidence: 99%
“…There still lacks e cient and effective treatment modalities for GBM dissemination control. Some polite studies revealed stereotactic radiosurgery (SRS) might be helpful for a single, small lesion with satisfactory disease control 17,45 . For eligible patients, SRS might be an ideal choice to alleviate suffering and prolong survival.…”
Section: Discussionmentioning
confidence: 99%